Metal pollution in surface sediments from Rodrigo de Freitas Lagoon (Rio de Janeiro, Brazil): Toxic effects on marine organisms - Vezzone, Mariana; Cesar, Ricardo; Moledo de Souza Abessa, Denis [UNESP]; Serrano, Aline; Lourenço, Rodrigo; Castilhos, Zuleica; Rodrigues, Ana Paula; Perina, Fernando Cesar [UNESP]; Polivanov, Helena (Elsevier, 2019)
The Rodrigo de Freitas Lagoon (RFL - Rio de Janeiro, RJ, Brazil) is a highly polluted and eutrophic lacustrine system, which has been often used for the practice of aquatic sports, including during the 2016 Summer Olympic Games. This study proposes the evaluation of metal concentrations in surface sediments from the RFL before and after urban interventions performed for the 2016 Olympics, as well as their toxicity to the benthic amphipod Tiburonella viscana and embryos of the sea-urchin Echinometra lucunter. Metal concentrations determined in 2017 were significantly higher than those obtained in 2015 (especially Cu, Cd and Ni), suggesting that the interventions performed to fulfill the requirements of the Olympics increased metal contents in sediments. The sediments from the northern sector of the RFL were muddier, more organically enriched, exhibited higher metal concentrations and were more toxic to T. viscana when compared to the sediments collected in the southern sector. This fact is particularly important since the practice of sports, including during the 2016 Olympics, has been preferably performed in the northern sector. Metal distribution was strongly correlated with organic matter and mud contents. The toxicity to E. lucunter embryos was high for both northern and southern sediments; most of the samples led to 100% lack or abnormal embryonic development. The integration of physical, chemical and ecotoxicological data indicates that the mortality to T. viscana was correlated with metal contents, whereas the toxicity to E. lucunter was apparently related to the release of ammonia from the sediment to water column. Finally, high metal concentrations and the toxicity to aquatic organisms evidence the ecological risks to the biota from RFL. High metal concentrations and the toxicity to aquatic organisms evidence the ecological risks to the biota from Rodrigo de Freitas Lagoon (Rio de Janeiro – Brazil).
Keywords: Amphipod; Bioassays; Contamination; Sea urchin; Toxicity